BACILLUS THURINGIENSIS: DIVERSIDADE GÊNICA EM ISOLADOS LEPIDOPTERA-ESPECÍFICOS - Guidelli-thuler, A.m [UNESP]; Sena, J.a.d. [UNESP]; Abreu, I.l. [UNESP]; Davolos, C.c. [UNESP]; Alves, S.b.; Polanczyk, R.a.; Valicente, F.h.; Lemos, M.v.f. [UNESP] (Instituto Biológico, 2022)
The aim of this work was to genetically characterize 1,073 isolates of B. thuringiensis, from three Brazilian collections – UNESP/Jaboticabal, ESALQ/Piracicaba and EMBRAPA/Sete Lagoas– with the main emphasis on the analysis of the cry1 gene types presented by these isolates. To achieve this purpose, oligonucleotide primers were designed based on 16 conserved and 4 unconserved regions of the corresponding sequences from each one of the 16 subclasses of the cry1 set of genes and used in PCR amplification assays. These sequences were amplified and the presence of amplicons for each subclass was evaluated in terms of percentage of gene type per bacterial collection. As a result, 55.7% of the isolates reacted to the primer Gral cry1, and the subclasses cry1Aa, cry1Ab, cry1Ac, cry1Ad, cry1Ae, cry1Af, cry1Ag, cry1Bf, cry1Ca and cry1Fa were detected in high percentages among the isolates ranging from 43.4 to 54.9%. A subclass distribution was observed among the set of isolates from these collections, with the greater percentage of isolates harboring the cry1Ab (42.12%) and the lowest percentage for thecry1Db subclass (0.6%). The genetic variability of the analyzed bacterial collections seems to indicate the ESALQ/Piracicaba and the UNESP/Jaboticabal subsets as sources of promising isolates for the control of Lepidoptera pest insects. For the EMBRAPA/Sete Lagoas subset of isolates, in which the evaluated subclasses frequencies were considered low (below 20%), the cry1B was the most frequently observed gene type present in 38.5% of the isolates.

O presente trabalho teve como objetivo caracterizar geneticamente 1.073 isolados de Bacillus thuringiensis, de três coleções brasileiras, provenientes da UNESP, Jaboticabal, da ESALQ/ Piracicaba e da EMBRAPA. Sete Lagoas, analisando os tipos de genes cry1 apresentados pelos isolados. Para isso, foram elaborados oligonucleotídeos iniciadores a partir de 16 regiões conservadas e 4 regiões não conservadas das seqüências de cada uma das 16 subclasses do gene cry1. Essas seqüências foram amplificadas por PCR e a presença de amplicons para cada subclasse foi calculada em porcentagem por gene e por coleção. Nessa análise, 55,7% dos isolados apresentaram amplificação para o gene cry1, e as subclassescry1Aa, cry1Ab, cry1Ac, cry1Ad, cry1Ae, cry1Af, cry1Ag, e cry1Bf, cry1Ca e cry1Fa estão presentes em alta proporção de isolados, variando de 43,4% a 54,9%. Verificou-se que existe uma distribuição das subclasses dentro do banco de isolados de B. thuringiensis em estudo, com maior porcentagem de isolados portadores dos genes cry1Ab (42,12%) e com menor porcentagem de representantes da subclasse cry1Db (0,6%). A variabilidade gênica, nas coleções analisadas, destaca as coleções de Jaboticabal e Piracicaba como fontes de isolados promissores para uso em programas de Controle Biológico de pragas da ordem Lepidoptera. A coleção de Sete Lagoas, na qual as freqüências das subclasses estudadas foram relativamente baixas (abaixo de 20%), destaca somente o gene cry1Ab, presente em 38,5% dos isolados desta coleção.
BACILLUS THURINGIENSIS: GENETIC DIVERSITY OF LEPIDOPTERA-SPECIFIC ISOLATES
Keywords: Genetic variability; cry gene; Bacillus thuringiensis; Variabilidade genética; gene cry; Bacillus thuringiensis